The Platform Carbonates of Monte Jouf, Maniago, and the Cretaceous Stratigraphy of the Italian Carnian Prealps - Nicola H.M. Swinburne; Adriano Noacco (Geologia Croatica, 2010)
The Late Cretaceous strata of Monte Jouf are reasonably pure, white limestones, and are part of the stratigraphic unit known as Calcari del Monte Cavallo. M. Jouf is the original locality of two genera of rudists Joufia and Colveraia, which are used as biostratigraphic markers for shallow water carbonate facies in central-western Tethys. The limestone sequence has been subdivided into 4 units on the basis of facies and these have been dated using Sr-isotope chronology. This technique gives an independent age for the units and of the fossils as they occur on M. Jouf, and thus provides an accurate and precise timescale to present the evolution of the palaeoenvironment in this part of the Adriatic Carbonate Platform. Unit 1 is Late Cenomanian, as dated by the caprinid rudist Caprinula boissyi. Unit 2 ranges from the earliest to middle/late of the Campanian according to the Sr-isotope results. Unit 3 is Late Campanian to Campanian/Maastrichtian boundary, as dated by Sr-isotopes. Unit 4 is of earliest Maastrichtian age (placing the Campanian/Maastrichtian boundary at the extinction of the planktonic foraminifer Globotruncana calcarata). Two main epochs of broad, shallow carbonate platforms, covered by a diverse rudist fauna with large individuals, including recumbent forms are noted. The first of these was in the Late Cenomanian and the second in the latest Campanian. The Late Cenomanian event was ended by downfaulting of the platform margin, possibly preceded by a regression. Sediment wedges then began to build out again over the Late Cenomanian deposits, though in the interval Turonian-Santonian sediment by-passed the M. Jouf area. In the latest Campanian platform carbonate deposition was ended by a regression and by subsequent downfaulting in the Maastrichtian and Palaeocene.